2010
DOI: 10.1371/journal.ppat.1000985
|View full text |Cite
|
Sign up to set email alerts
|

Integration Preferences of Wildtype AAV-2 for Consensus Rep-Binding Sites at Numerous Loci in the Human Genome

Abstract: Adeno-associated virus type 2 (AAV) is known to establish latency by preferential integration in human chromosome 19q13.42. The AAV non-structural protein Rep appears to target a site called AAVS1 by simultaneously binding to Rep-binding sites (RBS) present on the AAV genome and within AAVS1. In the absence of Rep, as is the case with AAV vectors, chromosomal integration is rare and random. For a genome-wide survey of wildtype AAV integration a linker-selection-mediated (LSM)-PCR strategy was designed to retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 77 publications
9
90
0
1
Order By: Relevance
“…Studies originally demonstrated targeted integration through Southern blot analysis, fluorescence in situ hybridization (FISH), and AAVS1-specific PCR (2,9,10). Two studies have used low-throughput genomic approaches, involving enzyme digestion, ligation-mediated PCR, and cloning, to investigate AAV integration (28,29). One study was unable to detect any integrants in AAVS1 (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies originally demonstrated targeted integration through Southern blot analysis, fluorescence in situ hybridization (FISH), and AAVS1-specific PCR (2,9,10). Two studies have used low-throughput genomic approaches, involving enzyme digestion, ligation-mediated PCR, and cloning, to investigate AAV integration (28,29). One study was unable to detect any integrants in AAVS1 (28).…”
mentioning
confidence: 99%
“…One study was unable to detect any integrants in AAVS1 (28). The other study found that AAVS1 integrations in exon 1 of PPP1R12C represented less than one percent of events, while integration in the general vicinity (within 100 kb) of AAVS1 accounted for less than 10 percent (29). Efforts to apply computational techniques to AAV integration have been limited by the small and biased data pools, which preclude thorough bioinformatics (29).…”
mentioning
confidence: 99%
“…En effet, l'intégration de l'AAV sauvage peut avoir lieu dans une zone très étendue, en amont et en aval du site AAVS1, et entraîner des modifications profondes du génome cellulaire (délétions, duplications) ainsi que des délétions des extrémi-tés du génome viral. Il est ainsi impossible de connaître, a priori, les séquences virales présentes au niveau des jonctions avec l'ADN Figure 3A) [20][21][22]. Cela s'explique par la présence dans le génome cellulaire de nombreux sites RBS reconnus par les protéines Rep de l'AAV.…”
Section: Le Virus Aav Sauvage Et Sa Capacité D'intégration Site-spéciunclassified
“…The RBS is made up of multiple repeats of the tetranucleotide sequence 5Ј-GCTC-3Ј or small variations of this sequence. Interestingly, most of the AAV serotypes have three contiguous repeats flanked by pseudo-repeats, a feature that is shared with AAVS1 (18). The site-specific integration process is contingent on the presence of the large regulatory proteins Rep78/Rep68, the AAVS1 site, and a cis-acting viral DNA sequence (1,17,19,20).…”
Section: Adeno-associated Virus (Aav)mentioning
confidence: 99%